2017
DOI: 10.1371/journal.pone.0187649
|View full text |Cite
|
Sign up to set email alerts
|

Laccase SilA from Streptomyces ipomoeae CECT 3341, a key enzyme for the degradation of lignin from agricultural residues?

Abstract: The role of laccase SilA produced by Streptomyces ipomoeae CECT 3341 in lignocellulose degradation was investigated. A comparison of the properties and activities of a laccase-negative mutant strain (SilA−) with that of the wild-type was studied in terms of their ability to degrade lignin from grass lignocellulose. The yields of solubilized lignin (acid precipitable polymeric lignin, APPL) obtained from wheat straw by both strains in Solid State Fermentation (SSF) conditions demonstrated the importance of SilA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Laccases (EC 1.10.3.2) are multicopper oxidoreductases (MCOs) widely distributed in nature. , The fact of not needing cofactors together with their oxidative capacity makes them an interesting tool for the functionalization of lignin . Bacterial laccases, mainly from Streptomyces , have been recently demonstrated to be key enzymes in the lignin solubilization by these microorganisms. , These enzymes gained attention in recent years because of their advantages to act at a wide range of pH and temperature and in the presence of high concentration of salts and inhibitors, in contrast with most of fungal laccases. , The recombinant laccase from Streptomyces ipomoeae (SilA) has shown to have a biotechnological value in the degradation of textile dyes that are harmful to the environment, degradation of emerging pollutants (quinolones), and degradation of Kraft pulp Eucalyptus , thus increasing the degree of whiteness in a biowhitening process . Moreover, Moya et al demonstrated that S.…”
Section: Introductionmentioning
confidence: 99%
“…Laccases (EC 1.10.3.2) are multicopper oxidoreductases (MCOs) widely distributed in nature. , The fact of not needing cofactors together with their oxidative capacity makes them an interesting tool for the functionalization of lignin . Bacterial laccases, mainly from Streptomyces , have been recently demonstrated to be key enzymes in the lignin solubilization by these microorganisms. , These enzymes gained attention in recent years because of their advantages to act at a wide range of pH and temperature and in the presence of high concentration of salts and inhibitors, in contrast with most of fungal laccases. , The recombinant laccase from Streptomyces ipomoeae (SilA) has shown to have a biotechnological value in the degradation of textile dyes that are harmful to the environment, degradation of emerging pollutants (quinolones), and degradation of Kraft pulp Eucalyptus , thus increasing the degree of whiteness in a biowhitening process . Moreover, Moya et al demonstrated that S.…”
Section: Introductionmentioning
confidence: 99%
“…Other relevant biomarkers for vegetation are the methoxyphenols, released from lignins during pyrolysis and widely used for the direct study this biopolymer (Meier & Faix, 1992;Galetta et al, 2014;Blánquez et al, 2017). Lignin is mainly composed by three precursors: pcoumaryl (H), coniferyl (G), and sinapyl (S) alcohols and their proportion differ between groups of plants; whereas the softwood lignin from gymnosperms is made up by G units, that in hardwood from angiosperms contains G and S, and grass lignin G, S and H units.…”
Section: Introductionmentioning
confidence: 99%
“…There were four genes were identified in the genome of NEAU-G5 T belonging to AAs family, which encoded cellobiose dehydrogenase (EC 1.1.99.18), glucose 1-oxidase (EC 1.1.3.4), aryl alcohol oxidase (EC 1.1.3.7), alcohol oxidase (EC 1.1.3.13) and pyranose oxidase (EC 1.1.3.10). Moreover, the genomic analysis of COG database showed that strain NEAU-G5 T contained a gene encoding laccase (YP_006807284), which was a key enzyme for the degradation of lignin from agricultural residues [52]. Therefore, genomic analysis also confirmed that strain NEAU-G5 T had the ability to decompose lignin.…”
Section: Resultsmentioning
confidence: 99%